Universal coverage for oral health care in 27 low-income countries: a scoping review - Yiqun Luan; Divesh Sardana; Ashiana Jivraj; David Liu; Nishmi Abeyweera; Yajin Zhao; Jacqueline Cellini; Michelle Bass; Jing Wang; Xinran Lu; Zheyi Cao; Chunling Lu (BMC, 2024)
Abstract Background Low-income countries bear a growing and disproportionate burden of oral diseases. With the World Health Organization targeting universal oral health coverage by 2030, assessing the state of oral health coverage in these resource-limited nations becomes crucial. This research seeks to examine the political and resource commitments to oral health, along with the utilization rate of oral health services, across 27 low-income countries. Methods We investigated five aspects of oral health coverage in low-income countries, including the integration of oral health in national health policies, covered oral health services, utilization rates, expenditures, and the number of oral health professionals. A comprehensive search was conducted across seven bibliographic databases, three grey literature databases, and national governments' and international organizations' websites up to May 2023, with no linguistic restrictions. Countries were categorized into "full integration", "partial integration", or "no integration" based on the presence of dedicated oral health policies and the frequency of oral health mentions. Covered oral health services, utilization rates, expenditure trends, and the density of oral health professionals were analyzed using evidence from reviews and data from World Health Organization databases. Results A total of 4242 peer-reviewed and 3345 grey literature texts were screened, yielding 12 and 84 files respectively to be included in the final review. Nine countries belong to "full integration" and thirteen countries belong to "partial integration", while five countries belong to "no integration". Twelve countries collectively covered 26 types of oral health care services, with tooth extraction being the most prevalent service. Preventive and public health-based oral health interventions were scarce. Utilization rates remained low, with the primary motivation for seeking care being dental pain relief. Expenditures on oral health were minimal, predominantly relying on domestic private sources. On average, the 27 low-income countries had 0.51 dentists per 10,000 population, contrasting with 2.83 and 7.62 in middle-income and high-income countries. Conclusions Oral health care received little political and resource commitment toward achieving universal health coverage in low-income countries. Urgent action is needed to mobilize financial and human resources, and integrate preventive and public health-based interventions.